(untitled) (Indonesian Contemporary Nursing Journal (ICON Journal), 2024)
Aims: Body dissatisfaction is a problem experienced by many adolescents today. Age can affect how adolescents perceive their body image. This study aimed to determine age differences in body dissatisfaction in adolescent girls who use Instagram face filters. Methods: The type of research used was descriptive, with a cross-sectional design; the researchers obtained 165 samples using the Slovin formula as respondents using a stratified random sampling technique. The level of body dissatisfaction was measured using the Multidimensional Body-Self Relations Questionnaire-Appearance Scale. Results: The results of univariate analysis using frequency distribution analysis showed that the majority of respondents had moderate levels of body dissatisfaction (24.2%), while the results of bivariate analysis using ANOVA test p-value = 0.820 (p> 0.05) showed no difference between age and the level of body dissatisfaction in adolescent girls. Conclusion: There is no difference in body dissatisfaction among adolescent girls who use Instagram filters. Each age has different stages of growth and development. Analysis of differences in body dissatisfaction levels for various age groups and analysis of body dissatisfaction levels for gender differences can also be carried out for further research.